Do English language learners know collocations? - Martyńska, Małgorzata (Investigationes Linguisticae, 2004)
This paper has a twofold purpose. First, to present the level of collocational competence among intermediate learners of the English language and to answer the question to what degree they know English collocations. With this goal in mind, a group of high school students was submitted to a test on collocation, whose results are shown in Section 2 of this paper. Second, to survey different linguistic attitudes towards the phenomenon of collocation and its categorization, as well as to emphasize the role of collocation in the process of second language learning.